AB0444 Impact of Gender on the Response and the Tolerance to Treatment with Abatacept in RA Patients: Results from the "Orencia and Rheumatoid Arthritis" Registry. (9th June 2015) - Nourisson, C.; Gottenberg, J.-E.; Mariette, X.; Mulliez, A.; Bardin, T.; Cantagrel, A.; Combe, B.; Dougados, M.; Flipo, R.-M.; Gaudin, P.; Vittecoq, O.; Schaeverbeke, T.; et al.
Abstract : Background: Sex differences in rheumatoid arthritis (RA) outcomes as well as response rate to many RA therapies have been established. Response to DMARD or TNF blockers is lower in women. Conflicting data with Rituximab have been obtained from French and British registers and no data beyond 6 months of follow up have been published with Abatacept. Objectives: Assess the impact of gender on the response and the tolerance with abatacept in RA patients. Methods: 1017 patients were included in The Orencia and Rheumatoid Arthritis (ORA) prospective registry, promoted by the French Society of Rheumatology. Disease activity (DAS28) was assessed at baseline and during follow-up (6, 12 and 24 months). The relationship between the EULAR response, DAS28 remission, rate of adverse events (at 6, 12 and 24 months) and gender was explored in multivariate analysis using a random effects model considering interaction between gender and time, subject random effect, adjustment on age, disease duration, Rheumatoid factor (RF) or anti-CCP positivity, current DMARDS or previous TNF blockers, corticoids use, RA activity, and potential impact of missing data. Results: 79.3% of the patients were female (age 57.3 years, disease duration 17 years [IQR 11-24]. RF and anti-CCP positivity was not different between females (69.8% and 68.5%) and males (76.9% and 75.5%). No difference was observed between sexes for the use of steroids (74.6%) or DMARDs (64.7%). At baseline, women had longer disease duration (p<0.001), higher disease activity (p=0.001), and had more often previously received anti-TNF drugs (p=0.04). The DAS28 remission rate was similar in the 2 sexes during the follow-up after adjustment on age, disease duration, RF or anti-CCP positivity, current DMARDS or previous TNF blockers, corticoids use, RA activity (Table 1 ). Patients with EULAR good-or-moderate response did not differ between men (52.4%) and females (55.5%). Moderate EULAR response was more frequent in women at 6 months but was no longer significant at 12 or 24 months. Time to achieving EULAR good-or-moderate response was similar in women and men (5.4±4.9 vs 5, 6±5.2 months, p=0.67). Treatment with abatacept was maintained similarly in 86.9, 72.5, 52.8% of men and 91.1, 72.8, 55.8% of women at the 6, 12, 24 month follow-up visits respectively.73.1% of women and 69.4% of men stopped at least one time the treatment during the follow-up (p=0.3) because of inefficacy in 72% and 64.4% respectively (p=0.09), of adverse events in 14% and 15% (p=0.76). Conclusions: In this large cohort of RA patients treated with Abatacept in real life, after 2 years of follow-up, similar rate of remission and good-or-moderate EULAR response were observed between men and women after adjustment on disease activity. Drug retention rate and safety were also comparable. Disclosure of Interest: None declared